International Standards in Teaching and Assessing the English Language (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores international standards in teaching and assessing the English language, with special emphasis on the Common European Framework of Reference for Languages (CEFR). It examines the structure of CEFR, its role in developing language skills, modern assessment approaches, and its significance in ensuring quality, transparency, and consistency in English language education worldwide.